PENGARUH KOMPOSISI PAKAN BUATAN TERHADAP PERTUMBUHAN LELE SANGKURIANG - Karolus Da Cruz; Yosy Gustasya; Daniel Candido Da Costa Soares (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine and analyze the effects of different artificial feed formulations on the growth performance, Feed Conversion Ratio (FCR), and Survival Rate (SR) of Sangkuriang catfish (Clarias gariepinus). An experimental method was employed using a Completely Randomized Design (CRD) consisting of four treatments and three replications: Treatment A (36.37% protein), Treatment B (32.23% protein), Treatment C (27.78% protein), and Treatment D (commercial feed as the control). The experiment was conducted for 30 days at the Kupang State Agricultural Polytechnic using catfish fingerlings with an initial length of approximately 7 cm and an average weight of approximately 3.0 g, reared in 26-L containers. Statistical analysis (ANOVA, P < 0.05) revealed that different feed formulations had a highly significant effect on all observed parameters. Treatment A produced the highest absolute length growth (3.76 cm) and the most efficient feed utilization, indicated by the lowest FCR value (1.11), which was statistically comparable to the commercial feed (Treatment D). Meanwhile, Treatment D resulted in the highest absolute weight gain (7.07 g) and specific growth rate (SGR) of 4.04%. The highest survival rate was achieved in Treatment C (93.3%), whereas the lowest survival rate was observed in Treatment D (56.6%), primarily due to environmental management factors and cannibalistic behavior. This study recommends the use of local feed formulation A for catfish culture because of its superior feed efficiency (lowest FCR) and its ability to compete with commercial feed performance. In addition, periodic size grading is recommended in bucket-based culture systems to minimize cannibalism and improve survival rates.